Morbidity of rectosigmoid resection in cytoreductive surgery for ovarian cancer. Risk factor analysis. Issue 6 (June 2018) - Fournier, M.; Huchon, C.; Ngo, C.; Bensaid, C.; Bats, A.S.; Combe, P.; le FrèreBelda, M.A.; Fournier, L.; Berger, A.; Lecuru, F.
Abstract: Aim: Rectosigmoid resection is often performed during cytoreductive surgery for ovarian cancer, to achieve the goal of no residual tumour. Here, we evaluated the morbidity associated with rectosigmoid resection and the underlying risk factors. Methods: We retrospectively assessed consecutive patients managed with rectosigmoid resection during cytoreductive surgery for ovarian cancer at our centre in Paris, France, between 2005 and 2013. All previously identified risk factors were analysed. Major complications were defined as grade III-IV in the Clavien-Dindo classification. Results: Of 228 patients, 116 had primary and 112 interval surgery; 43/228 [18.9%]; experienced major complications, and these were more common after primary surgery [24.1% vs. 13.4%, p = .04]. The 69 patients who had rectosigmoid resection [33 primary vs. 36 interval surgery, p = .32] had a higher morbidity rate compared to the other patients [30.4% vs. 14.6%, p = .006]. The anastomotic leakage rate was 2.89%. By multivariate logistic regression, independent risk factors for morbidity were postmenopausal status [adjusted odds ratio (aOR), 13.7; 95% confidence interval (95%CI), 1.2;161.9], surgery after neoadjuvant chemotherapy [aOR, 4.4; 95%CI, 1.1;18.8], and peritoneal stripping of the left; paracolic gutter [aOR, 11.3; 95%CI, 2.3;54.3]. Conclusion: The morbidity of rectosigmoid resection during cytoreductive surgery for ovarian cancer seems acceptable. Ileostomy does not seem associated with a lower risk of major complications or adjuvant bevacizumab with a higher complication rate.